Pemberdayaan Subak Penarungan sebagai Lembaga Agribisnis di Desa Penarungan, Kecamatan Mengwi, Kabupaten Badung - DARMAYASA, NYOMAN EDY; PARINING, NYOMAN; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
Empowerment of Subak Penarungan as an Agribusiness Institution in Penarungan Village, Sub-District of Mengwi, Badung Regency The preservation of subak or Balinese irrigation organization is important because its sustainability in Bali based on the Tri Hita Karana concepts. Subak-based economic business is a food-based agribusiness or paddy fields. The studies on empowerment of subak as an agribusiness institution aimed to improve the economy and welfare of farmers, so that the agricultural culture is in demand and not abandoned by the Subak Penarungan community. This study aimed to determine (1) the potentials of subak related to natural resources, human resources, and financial resources, (2) the efforts made to empower Subak Penarungan as an agribusiness institution. The research was conducted in Subak Penarungan, Mengwi Sub-district, Badung Regency. The selection of research site was done purposively. The population of this study is active members of Subak Penarungan, amounting to 167 people. The sample size was determined by using Slovin formula, so the number of respondents was 63 people. The data analysis used a descriptive qualitative analysis method. The findings showed that the potential of Subak penarungan was in good category with the average score of 3.55, and the results of research on the efforts of empowerment of Subak Penarungan was in good category, with average achievement score of 3.50. Based on the results of this study, it can be suggested to farmers that the assistance in the form of agricultural machine tools provided by the government for subak should be utilized properly, so as to increase their productivity.